NILAI-NILAI PENDIDIKAN DALAM IBADAH PUASA - M Shabir Umar (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2011)
Fasting is one of forms of devotion to Allah which must be fulfilled by a Muslim. Fasting is done by abstaining from food, drink, and sexual intercourse from the dawn to sun sets. Fasting is done to prove a sincere belief to the Almighty God. In addition, fasting contributes some values of education; they are health and character education. Health education is due to the fact that the body needs to take a rest by fasting after continuously work for one year to process the food from day to day. Fasting can also reduce potential diseases. This is in accordance with medical research findings. Cha-racter education may also be actualized by fasting, particularly when the one who does fasting should be discipline and honest.